IMPLEMENTASI MEDIA FLASH CARD MENSTIMULASI PERKEMBANGAN ANAK USIA DINI PAUD CAHAYA GENERASI BANGSA PONTIANAK - Andani, Melinia; Miranda, Dian; Lukmanulhakim, Lukmanulhakim (Universitas Tanjungpura, 2025)
This research aims to describe the implementation of flash card media in stimulating six aspects of early childhood development 4-5 years old at the Cahaya Generasi Bangsa PAUD, Southeast Pontianak. The problem in this research is the implementation of flash card media in stimulating six aspects of child development, namely the use of flash card media for the development of religious and moral values, physical motoric, cognitive, language, social emotional and artistic. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. The research results show that flash card media can stimulate the development of religious and moral values, physical motor, cognitive, language, social emotional and artistic in early childhood. The application of this media has been proven to increase children's understanding and skills in various aspects of development. Apart from that, flash card media can be an effective tool in stimulating six aspects of early childhood development. Using this media can help children understand concepts better through an attractive visual approach. Therefore, it is recommended that educators use this media more often in learning activities.